2018
DOI: 10.1029/2018jd028535
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cloud Microphysical Properties Derived From MODIS and CALIPSO With In Situ Measurements Over the Wintertime Southern Ocean

Abstract: In situ observations of cloud effective radius (r eff ), droplet number concentration (N d ), and thermodynamic phase from 11 wintertime flights over the Southern Ocean (43-45°S, 145-148°E) are compared to products from MODerate-resolution Imaging Spectroradiometer (MODIS) and Cloud-Aerosol Lidar with Orthogonal Polarization. The in situ observations were in close alignment with A-train overpasses for a 30-min window. For open mesoscale cellular convection, which was predominantly observed, clouds were commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 77 publications
(143 reference statements)
9
50
0
Order By: Relevance
“…The hemispheric constraint depends on the accuracy of the satellite-derived values of PD N d . As noted in the Introduction, MODIS N d has been extensively validated against aircraft measurements in the NH and parts of the SH (21,28,29). Because aircraft observations of N d are not as plentiful in the more remote regions of the SO, we use other datasets to provide additional assessment of the quality and the believability of the surprising SO MODIS N d pattern (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemispheric constraint depends on the accuracy of the satellite-derived values of PD N d . As noted in the Introduction, MODIS N d has been extensively validated against aircraft measurements in the NH and parts of the SH (21,28,29). Because aircraft observations of N d are not as plentiful in the more remote regions of the SO, we use other datasets to provide additional assessment of the quality and the believability of the surprising SO MODIS N d pattern (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The N d derived from satellite retrievals has been shown to be reasonably unbiased in comparison with aircraft measurements (21,(24)(25)(26)(27)(28) and to agree well in both the remote Southern Ocean (SO) (29) and the NH (28). Biases between in situ and N d calculated based on Moderate Resolution Spectroradiometer (MODIS) data are on the order of 1 cm −3 to 20 cm −3 , depending on geographic region and boundary layer stratification, and systematic bias does not scale strongly with N d (27)(28)(29). The hemispheric contrast in N d is a difference, so this should moderate the effects of any systematic biases in N d .…”
Section: Significancementioning
confidence: 90%
“…The Re biases reported in Figures g and g compare very well with the few existing in situ validation studies of MODIS Re 2.1 . For example, using data from the VAMOS Ocean‐Cloud‐Atmosphere‐Land Study Regional Experiment (VOCALS‐REx) in the Southeast Pacific during October to November 2008 (region ① in Figure g), Painemal and Zuidema () showed an ~1 to 2 μm bias in MODIS Re 2.1 ; from the Rain in Cumulus over the Ocean (RICO) field campaign from November 2004 to January 2005 (region ② in Figure g), Haney () showed MODIS Re 2.1 biases ranging from ~7 to 12μm, and aircraft observations in the southern ocean (region ③ in Figure g) from June to October in 2013 to 2015, Ahn et al () showed an overestimate in MODIS Re 2.1 of ~13 μm on average for nondrizzling clouds. All of these studies line up nicely with the regional Re 2.1 biases shown in Figures g and g.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison between MODIS-retrieved Re and in situ observations shows that overestimates in MODIS Re range from about −0.22 to 13 μm, depending on cloud type, Sun-view geometry, the choice of in situ probe, and the details of the cloud microphysical properties (e.g., Ahn et al, 2018;Glienke et al, 2017;King et al, 2013;Painemal & Zuidema, 2011;Witte et al, 2018). In particular, Witte et al (2018) suggested that while satellite retrievals are commonly validated against in situ measurements, the uncertainty of the aircraft retrievals should be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Painemal and Zuidema (2011) found that the Moderate Resolution Imaging Spectroradiometer (MODIS) retrievals overestimated the cloud droplet r e by about 15–20% or 2.1 μm compared to in situ aircraft observations for marine stratocumulus over the Southeast Pacific. Ahn et al (2018) found that CALIPSO and MODIS underestimated mixed‐phase cloud occurrence, and MODIS (2.1‐μm channel) overestimated r e by about 13 μm for nondrizzling clouds and by about 10 μm for heavy drizzling cases. Using different near‐infrared bands, the satellite‐based r e could also vary significantly due to the different photon penetration depths.…”
Section: Introductionmentioning
confidence: 99%